Gestión de inventario en la Empresa AUTOPARTES MB del cantón Quevedo Provincia de Los Ríos - Gaibor Monserrate, Sandra Yulissa (2021)
The company Autopartes "MB" from the city of Quevedo has weaknesses in inventory management due to inadequate administrative management carried out by the human talent of the organization. The objective of the research is to analyze the inventory management of the company “Autopartes MB and the influence it has on decision-making by the directors of the institution. The methodology is made up of deductive and inductive methods, which allowed the particular analysis of the consequences generated by inadequate inventory management; The types of research are field and documentary, while the techniques used are interview and direct observation, which made it possible to identify the main findings in the inventory control of the company “Autopartes MB”. The results of the investigation are: the administration does not have an inventory system that allows automating internal procedures, the registration of goods is executed through the Office Excel tool, the physical space to store the goods is limited and the talent Human does not have administrative and accounting competencies, document management is scattered, there are no technological tools that allow information to be centralized and the products with the highest and lowest turnover are unknown.